The Validity of Some Popular Readability Formulas - Heydari, Pooneh (Richtmann Publishing, 2012)
This study aimed at exploring the correlation between readers’ evaluation of text-readability on one hand and somepopular readability formula’s (Flesch Reading Ease Readability Formula, Gunning’s Fog-Index of Readability, The SMOG Indexof Readability, Flesch-Kincaid) evaluation of text-readability on the other. This study was conducted with an overall number of118 participants. The participants were selected from among male and female undergraduate students studying different EFLrelatedmajors at the Department of Foreign Languages and Linguistics of IAU, Shiraz Branch. The participants were chosenusing convenient sampling procedure. To achieve the objectives of the study, 5 passages of different readability index wereused. Moreover, a questionnaire aimed at tapping responses from the participants was devised on each passage. Finally, anumber of SPSS analyses were run and the results of the study did not reveal any significant correlations between readers’ andthe formulas’ evaluation of text-readability level. As a conclusion, it seems that those teachers who have used the readabilityformulas as valuable measures for evaluating materials to use with their students should use them cautiously. Of course, furtherresearch seems necessary to check the validity of the readability formulas.